Kinesiotaping: Innovation in handling injuries to athletes - Awaluddin Awaluddin; Juhanis Juhanis; Benny Badaru; Ishak Bachtiar; M Said Zainuddin (Universitas Muhammadiyah Magelang, 2025)
Injuries can occur due to direct physical pressure, excessive use of body parts, or accidental trauma during training and competition. Kinesiotaping is a method that can be used as a preventive and rehabilitative measure for injuries, thus helping athletes improve their performance, skills, and achievements in sports. However, Petanque athletes in South Sulawesi Province still have limited understanding of the application of kinesiotaping as an innovation in the treatment and rehabilitation of sports injuries. Therefore, the purpose of this Community Service (PkM) is to provide education and practice of installing kinesiotaping to Petanque athletes in South Sulawesi Province. The method used is service learning (SL), which consists of three stages: pre-implementation, implementation, and post-implementation. The results of this activity show an increase in athletes' understanding and skills related to kinesiotaping. As many as 76.66% of participants now know about kinesiotaping, while 80% of participants know how to install kinesiotaping. Thus, it can be concluded that there is an increase in athletes' understanding and knowledge regarding the benefits and methods of installing kinesiotaping as an innovation in the prevention and treatment of sports injuries.